Temporal Whole-Transcriptomic Analysis of Characterized In Vitro and Ex Vivo Primary Nasal Epithelia - Legebeke, Jelmer; Horton, Katie L.; Jackson, Claire L.; Coles, Janice; Harris, Amanda; Wai, Htoo A.; Holloway, John W.; Wheway, Gabrielle; Baralle, Diana; Lucas, Jane S. (Frontiers in Cell and Developmental Biology, 2022)
Air-liquid interface (ALI) cell culture of primary airway progenitors enables the differentiation and recapitulation of a pseudostratified epithelium in vitro, providing a highly useful tool for researching respiratory health and disease. Previous studies into gene expression in ALI-cultures compared to ex vivo nasal brushings have been limited in the number of time points and/or the number of genes studied. In this study physiological and global transcriptomic changes were assessed in an extended in vitro 63-day human healthy nasal epithelium ALI-culture period and compared to ex vivo nasal brushing samples. Ex vivo nasal brushing samples formed distinct transcriptome clusters to in vitro ALI-cultured nasal epithelia, with from day 14 onwards ALI samples best matching the ex vivo samples. Immune response regulation genes were not expressed in the in vitro ALI-culture compared to the ex vivo nasal brushing samples, likely because the in vitro cultures lack an airway microbiome, lack airborne particles stimulation, or did not host an immune cell component. This highlights the need for more advanced co-cultures with immune cell representation to better reflect the physiological state. During the first week of ALI-culture genes related to metabolism and proliferation were increased. By the end of week 1 epithelial cell barrier function plateaued and multiciliated cell differentiation started, although widespread ciliation was not complete until day 28. These results highlight that time-points at which ALI-cultures are harvested for research studies needs to be carefully considered to suit the purpose of investigation (transcriptomic and/or functional analysis).